Development, evaluation, and optimization of flurbiprofen nanoemulsions gel using quality by design concept - Aiswarya, Prof. G. (Asian Journal of Pharmaceutics (AJP), 2015)
The objective of this study was to formulate topical gel loaded nanoemulsions containing flurbiprofen using volatile oil.Â The gel released the drug at a controlled rate to the targeted site. Flurbiprofen (log P = 4.09) in generally used forÂ transdermal treatment of rheumatoid arthritis and osteoarthritis. Selection of the oil phase, surfactant, and cosurfactant wasÂ done by individual screening method with the aid of pseudoâ€ternary phase study. International Conference on HarmonisationÂ Q8 guidelines was applied using 32 factorial designs coupled with response surface methodology. The formulations wereÂ prepared by using spontaneous emulsification method. The selected formulation from various statistical and other studiesÂ was investigated. It was found that selected formulation showed an optimum inâ€vitro data. Later the optimized formulationÂ obtained within the tentative design space was incorporated in the gel and compared with the marketed formulation.The resultÂ suggested the optimized formulation with good potential for transdermal delivery of the drug than the marketed formulations. Key words: Design space, flurbiprofen, inâ€vitro diffusion, nanoemulsions, transdermal drug delivery